AKTIVITAS PEMANFAATAN GUA DAN CERUK DI NAGARI SITUMBUK, TANAH DATAR - SUMATERA BARAT - Nenggih Susilowati (Balai Arkeologi Sumatera Utara, 2019)
Nagari Situmbuk, Salimpaung Subdistrict, Tanah Datar District, West Sumatra Province has naturally interesting caves and rock shelters, and their existence is also related to past and present human activities. The caves and rock shelters in the Situmbuk area are partly related to human activities that use them as temporary dwellings.Its existence is also related to human activities that utilize the surrounding environment as rice fields, plantations and tropical forests. The problem raised is how is the form of human activity related to the use of caves and rock shelters in Nagari Situmbuk in the past? Why is there a difference in the use of caves and rock shelters there? The method used in this research is qualitative using inductive reasoning flow by observing the unit and its context. The caves and rock shelters which have indications of being used by people with different cultures are Ngalau Guong, Ngalau Tompok Syohiah I, and Ngalau Muaro. The use of Ngalau Guong is related to hunting life and simple farming so that it still utilizes caves / rock shelters there as temporary dwellings. Ngalau Tompok Syohiah I is related to the development of Pre-Islamic culture (megalithic tradition which is marked by the presence of menhirs and pseudo graves), Islam, until now which is implied through symbols on the walls of the cave. The tradition that takes place in the cave is also related to agricultural activities that have been carried out intensely. Then Ngalau Muaro, this relates to plantation activities that took place around the 18th century to the 19th.